2004
DOI: 10.1093/bioinformatics/bth381
|View full text |Cite
|
Sign up to set email alerts
|

Differences in gene expression between B-cell chronic lymphocytic leukemia and normal B cells: a meta-analysis of three microarray studies

Abstract: We introduce a statistical approach within a Bayesian framework to combine the microarray data on matched genes from three investigations of gene expression profiling of B-cell chronic lymphocytic leukemia (CLL) and normal B cells (NBC) using three different microarray platforms, oligonucleotide arrays, cDNA arrays printed on glass slides and cDNA arrays printed on nylon membranes. Using this approach, we identified a number of genes that were consistently differentially expressed between CLL and NBC samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 51 publications
0
80
1
Order By: Relevance
“…A recent metaanalysis of three microarray studies comparing gene expression between chronic lymphocytic leukemia and normal B cells also found that TNFRSF7 and TNFRSF1B were overexpressed in chronic lymphocytic leukemia, 31 although similar findings have not been reported for follicular lymphoma. TNFRSF7 interacts with CD40 to inhibit apoptosis in B cells.…”
Section: Mcl1 Wasmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent metaanalysis of three microarray studies comparing gene expression between chronic lymphocytic leukemia and normal B cells also found that TNFRSF7 and TNFRSF1B were overexpressed in chronic lymphocytic leukemia, 31 although similar findings have not been reported for follicular lymphoma. TNFRSF7 interacts with CD40 to inhibit apoptosis in B cells.…”
Section: Mcl1 Wasmentioning
confidence: 90%
“…Indeed, this practice is not uncommon in studies using group analysis. 23,31 We recognize that gene expression microarrays provide in vitro data primarily for generation of hypothesis. Thus, we have validated the upregulation of survivin in postchemotherapy chronic lymphocytic leukemia tumor samples with an in vivo method, immunohistochemistry.…”
Section: Mcl1 Wasmentioning
confidence: 99%
“…Indeed, cancer has been associated with alterations in the epigenetic code leading to abnormal gene expression. 37 In 2004, Wang et al 38 conducted a meta-analysis comparing CLL with normal B-cell gene expression profiles and identified a number of genes that were differentially expressed between CLL and normal samples. Several genes described as overexpressed in CLL (for example, CD5, BCL2, CD23, LCK and PIM1) were downregulated by VPA, whereas genes described as underexpressed in CLL (for example, BCLA1, c-MYC, DUSP2 and PEA15) were upregulated by VPA.…”
Section: Gene Expression Profile Of Vpa-treated Cll B Cells B Stamatomentioning
confidence: 99%
“…Differential expression was identified to be similar to that described by Wang et al (16). We used Z values (defined below) to assess differentially expressed genes between current and never or former smokers, in whom the magnitude of the Z values is assumed to represent the effect of smoking cessation.…”
Section: Identification Of Differentially Expressed Genesmentioning
confidence: 99%
“…The permutation was done within each of the data sets, but never across the data sets. Note that other than the permutation step, our method is the same as that described by Wang et al (16).…”
Section: Smoking Cessation and Global Gene Expressionmentioning
confidence: 99%